2019
DOI: 10.1111/odi.13070
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2 is a prognostic marker and its silencing inhibits recurrence in ameloblastomas

Abstract: Objectives Ameloblastomas are the most common odontogenic epithelial tumors with high recurrence rate. The aim of this study was to identify apoptosis‐related genes with recurrence of ameloblastomas and to evaluate its feasibility as a prognostic marker and as a target molecule preventing from recurrence. Materials and Methods Public microarray data were analyzed. To evaluate their expression in ameloblastoma patients, immunohistochemical staining was performed in 89 human ameloblastoma tissues. Quantitative P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Ameloblastoma (AB), the most common odontogenic epithelial tumor, has locally aggressive propensity and a high rate of postoperative recurrence rate (Kim et al., 2019). Among all the categories of odontogenic epithelial tumors, AB has the highest incidence rate (approximately 30%–40%) in developing countries (Ahire et al., 2018; Fernandes et al., 2005), reaching 76.5% in the African population (Oginni et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ameloblastoma (AB), the most common odontogenic epithelial tumor, has locally aggressive propensity and a high rate of postoperative recurrence rate (Kim et al., 2019). Among all the categories of odontogenic epithelial tumors, AB has the highest incidence rate (approximately 30%–40%) in developing countries (Ahire et al., 2018; Fernandes et al., 2005), reaching 76.5% in the African population (Oginni et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bcl‐2 expression in granular cells, found in our study, was reported by Meer et al and Mesquita et al, 8,11 while Bcl‐2 negativity was detected only by Chiang et al 4 Furthermore, Meer et al found Bcl‐2 positivity also in the odontogenic epithelium, these data suggest that there is variability in the expression of this protein. In keratocyst and ameloblastoma bcl‐2 expression seems to be associated with a higher rate of recurrence and aggressive behaviour, Bcl‐2 may play a role also in the expansion of this tumour 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…For each section, three fields were randomly selected (×200). The expression scores of Beclin1, LC3, and LAMP2 were on the grounds of staining intensity (no coloring: 0 point; light yellow: 1 point; brown yellow: 2 points; sepia: 3 points) and percentage of positive tumor cells (0–5%: 0 point; 6–25%: 1 point; 26–50%: 2 points; >50%: 3 points) ( 17 ). The final score was determined by staining intensity score × percentage of positive tumor cells (>4 scores: positive and 0–3 scores: negative).…”
Section: Methodsmentioning
confidence: 99%